Velocimetric characterization of a 30 sec maximal test in swimming: Consequences for bioenergetical evaluation - Soares, S.; Machado, L.; Lima, A.; Santos, I.; Fernandes, R.; Correira, M.; Maia, J.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to characterize the velocity curves corresponding to 30 sec maximal front crawl swimming, and to establish eventual relationships with metabolic path-ways related to the anaerobic energy production. 72 swimmers of different maturational Status were studied. The mathematical procedures for data treatment, including a continuous wavelet analysis, are described. Results revealed a tendency to an inverse relationship between the number of fatigue thresh-olds found on the velocity curves and the maturational Status. The large number of the velocity curves studied presented two fatigue thresholds. The first threshold was found between 8 and 12 sec. This time interval well fits the alactic-lactic threshold enounced in the literature and leads us to speculate about the possibility of using the velocity curves to assess individual alactic-lactic thresholds in order to better plan and control anaerobic swimming training.